Synthesis of Organic Molecules, R Ribose and S Amino Acids by Adsorption on Carbon at The Birth of Life on The Earth - Zhmakin, Vladimir (European Scientific Journal, ESJ, 2016)
Reasons for appearance of optically active organic molecules in nature have not been ascertained up to the present, but clarification of conditions on the Earth during the period of their appearance can contribute to this. H2 and gases, containing H2, were oxidized by CO2 with allocation of carbon and H2O or CH2O and СНO(OН) in volcanic gas and in the early atmosphere. During adsorption on carbon CH2O dissolved in water could be the synthesis only of R (rectus, Latin) ribose, and with NH3 and СНO(OН) synthesis of glycine and only of S (sinister) serine, and on its bases of other S amino acids. Adsorption on the carbon ensured in complex: concentration of initial components, hydrophobic-hydrophilic properties, optical purity, protection from hydration, decay and racemization. It is shown the possibility of the early Archean reactions: dehydration of phosphoric acid, of phosphoester bonds connection formation in nucleotides, with CH2O fatty acids and nitrogenous bases.